Maternal education and early child development: The roles of parental support for learning, learning materials, and father characteristics - Yusuf Emre Akgündüz; Şaziye Pelin Akyol; Abdurrahman Aydemir; Murat Demirci; Murat G. Kirdar (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper explores the intergenerational effects of maternal education on the development outcomes of 24- to 59-month-old children in Turkey. As the source of exogenous variation in maternal schooling, we use mothers' exposure to the 1997 education reform in Turkey, which extended the duration of compulsory schooling from 5 to 8 years. The data come from the 2018 Turkey Demographic and Health Survey, which has a rich special module on early child development. We find a substantial increase in mothers' educational attainment and a rise in children's readiness to learn. Our finding is novel because it measures readiness to learn at a very young age rather than cognitive skills at later ages, as the previous studies do. We also find suggestive evidence of a positive impact on children's social-emotional development. Examining the channels, we find that both mothers and fathers, particularly fathers, spend more time with their children, and the variety of activities parents engage with them rises. In addition, learning materials at home, such as books, rise. Also, exploring father outcomes, we find evidence of reductions in the schooling and age gaps between partners, implying an increase in women's bargaining power, and suggestive evidence of a rise in fathers' schooling. These findings about father outcomes are consistent with the significant rise in fathers' involvement with children.
Keywords: I26; J13; J24; 330; maternal education; early child development; parental support for learning